2006
DOI: 10.1128/aac.00019-06
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Emergence of Resistance in Clostridium difficile during Treatment of C. difficile -Associated Diarrhea with Fusidic Acid

Abstract: Samples from patients with Clostridium difficile-associated diarrhea (CDAD) that were randomized to fusidic acid (n ‫؍‬ 59) or metronidazole (n ‫؍‬ 55) therapy for 7 days were cultured for Clostridium difficile in feces on days 1, 8 to 13, and 35 to 40. Of the patients who were culture positive only before treatment, 77% (36/47) were permanently cured (no treatment failure and no clinical recurrence), compared to 54% (22/41) of those with persistence of C. difficile at one or both follow-ups (P ‫؍‬ 0.03). A si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 42 publications
(36 reference statements)
0
30
0
Order By: Relevance
“…Although not approved for use, other drugs, such as rifaximin and fusidic acid, against which high-frequency single-step resistance can be selected in C. difficile, are occasionally used to treat CDI. Attempts to understand the impact of mutants with reduced susceptibility to these agents on therapeutic outcome have been reported (Noren et al 2006;Mattila et al 2013). For example, a study comparing fusidic acid with metronidazole for the treatment of CDI showed that although all isolates from patients randomized to fusidic acid were susceptible at baseline, 55% (11/20) of posttreatment isolates were resistant to fusidic acid (median MIC .256 mg/mL) (Noren et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although not approved for use, other drugs, such as rifaximin and fusidic acid, against which high-frequency single-step resistance can be selected in C. difficile, are occasionally used to treat CDI. Attempts to understand the impact of mutants with reduced susceptibility to these agents on therapeutic outcome have been reported (Noren et al 2006;Mattila et al 2013). For example, a study comparing fusidic acid with metronidazole for the treatment of CDI showed that although all isolates from patients randomized to fusidic acid were susceptible at baseline, 55% (11/20) of posttreatment isolates were resistant to fusidic acid (median MIC .256 mg/mL) (Noren et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Of 44 patients treated with fusidic acid in our previous study (16), 20 (45%) had C. difficile persisting at follow-up, and 11 (55%) of these patients carried fusidic acidresistant C. difficile isolates (n ϭ 12) ( Table 1). These isolates were selected for study, together with the resistant isolates recovered both pre-and posttherapy from one patient randomized to metronidazole (Table 1, patient 12) but who had received fusidic acid 2 weeks before inclusion in the study.…”
mentioning
confidence: 99%
“…The in vitro susceptibility of C. difficile to fusidic acid is generally excellent (4,11), and like for metronidazole, the high fusidic acid absorption (98%) (24) presumably results in sufficient therapeutic concentrations in feces from an inflammatory mucosa. However, we recently found that 55% of the fusidic acid-treated CDAD patients with posttherapy persistent C. difficile carried fusidic acid-resistant isolates of identical PCR ribotypes at follow-up (16). Our aims were to identify fusA of C. difficile, to explore the heterogeneity of the gene, and to find mutations associated with the emergence of fusidic acid resistance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on PCR analysis, the epidemic strain was designated ribotype 27 or NAP1/027 (19), which is distinguished from other strains by increased production of toxins, fluoroquinolone resistance, and production of binary toxin CDT, a third C. difficile toxin that has been associated with increased disease severity (12). Additionally, resistance development to several C. difficile agents has further complicated treatment (9,21,23).…”
mentioning
confidence: 99%